2018
DOI: 10.1111/bju.14510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positioning on ureteric stone retropulsion: ‘gravity works’

Abstract: Alterations in the angle of inclination reduced stone retropulsion during ureteroscopic lithotripsy in an in vitro model to <1 cm. Increasing the incline angle of a patient may effectively preclude retropulsion when performing laser lithotripsy of ureteric stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, in most in vitro studies, retropulsion is investigated via indirect methods which include pendulums [5,6], angled glass channels and flat glass setups [1,3,4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and vertical set-ups [22,23]. Through these indirect methods, there are several factors potentially influencing the results such as fluid dynamics, the impact's exact location, and the test body's irregular surface and composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most in vitro studies, retropulsion is investigated via indirect methods which include pendulums [5,6], angled glass channels and flat glass setups [1,3,4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and vertical set-ups [22,23]. Through these indirect methods, there are several factors potentially influencing the results such as fluid dynamics, the impact's exact location, and the test body's irregular surface and composition.…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study, Patel et al showed that the inclination of the patient on the operating table can preclude the development of push-ups during ureteroscopy. 11 Zehri et al reported that gel instillation to the proximal part of the stone increased stonefree rates. 12 Dretler demonstrated that a ureteral balloon advanced over a guidewire to the proximal part of the stone is useful in averting push-up.…”
Section: Discussionmentioning
confidence: 99%
“…To address this problem, various manipulations and antiretropulsion devices or techniques were developed. In an experimental study, Patel et al [11] showed that the inclination of the patient on the operating table can preclude the development of push-ups during ureteroscopy. Zehri et al [12] reported that gel instillation to the proximal part of the stone increased stone-free rates.…”
Section: Discussionmentioning
confidence: 99%